ADMA predicts major adverse renal events in patients with mild renal impairment and/or diabetes mellitus undergoing coronary angiography. Issue 6 (February 2017) - Heunisch, Fabian; Chaykovska, Lyubov; von Einem, Gina; Alter, Markus; Dschietzig, Thomas; Kretschmer, Axel; Kellner, Karl-Heinz; Hocher, Berthold
Abstract : Abstract: Asymmetric dimethylarginine (ADMA) is a competitive inhibitor of the nitric oxide (NO)-synthase and a biomarker of endothelial dysfunction (ED). ED plays an important role in the pathogenesis of contrast-induced nephropathy (CIN). The aim of our study was to evaluate serum ADMA concentration as a biomarker of an acute renal damage during the follow-up of 90 days after contrast medium (CM) application. Blood samples were obtained from 330 consecutive patients with diabetes mellitus or mild renal impairment immediately before, 24 and 48 hours after the CM application for coronary angiography. The patients were followed for 90 days. The composite endpoints were major adverse renal events (MARE) defined as occurrence of death, initiation of dialysis, or a doubling of serum creatinine concentration. Overall, ADMA concentration in plasma increased after CM application, although, there was no differences between ADMA levels in patients with and without CIN. ADMA concentration 24 hours after the CM application was predictive for dialysis with a specificity of 0.889 and sensitivity of 0.653 at values higher than 0.71 μmol/L (area under the curve: 0.854, 95% confidential interval: 0.767–0.941, P < 0.001). This association remained significant in multivariate Cox regression models adjusted for relevant factors of long-term renal outcome. 24 hours after the CM application, ADMA concentration in plasma was predictive for MARE with a specificity of 0.833 and sensitivity of 0.636 at a value of more than 0.70 μmol/L (area under the curve: 0.750, 95% confidence interval: 0.602–0.897, P = 0.004). Multivariate logistic regression analysis confirmed that ADMA and anemia were significant predictors of MARE. Further analysis revealed that increased ADMA concentration in plasma was highly significant predictor of MARE in patients with CIN. Moreover, patients with CIN and MARE had the highest plasma ADMA levels 24 hours after CM exposure in our study cohort. The impact of ADMA on MARE was independent of such known CIN risk factors as anemia, pre-existing renal failure, pre-existing heart failure, and diabetes. ADMA concentration in plasma is a promising novel biomarker of major contrast-induced nephropathy-associated events 90 days after contrast media exposure.